Stockist and dropship management system with SMS notification for Dian Legacy Sdn Bhd / Nik Yasmin Nik Nubli - Nik Nubli, Nik Yasmin (Faculty of Computer and Mathematical Sciences, 2017)
The development of this project is meant for the stockist and dropship agent of Dian Legacy SDN BHD. Currently, they are using Microsoft Excel in managing their online business transactions. Through interview that has been conducted with the stakeholder, stockist stated that it is hard to monitor the current stock as the stock quantity for their products. Moreover, it is also difficult for dropship agents to directly check the current stock for a particular product ordered by the customer as they do not have complete controls of the inventory. Lastly, it is found difficult for stockist and dropship agent to manage customer’s details and orders. Stockist and dropship agent management system for Dian Legacy SDN BHD with SMS notification is a web-based system that will assist online business communication and management between stockist and dropship agents in conducting business transactions. The management system were developed with three (3) objectives to be achieved. First objective was to identify the requirements for developing the system. Next objective is to develop an online stockist system to manage transaction between stockist and dropship agents. Last but not least is to evaluate the functionality of management system based on the requirements gathered. The methodology used to assist this project is the V-Shaped Model System Development Life Cycle (SDLC), which contains 3 phases; Verification, Programing as well as Validation. One of the deliverables from the phases is the Software Requirements Specification that is the basis in producing the design documentation. The results and discussion was carried out and the objectives of this project is met and tally with the phases in methodology. However, the system has some limitation and possible future enhancement has been discussed.